1997
DOI: 10.1007/s004310050743
|View full text |Cite
|
Sign up to set email alerts
|

In vitro release of eosinophil cationic protein from peripheral eosinophils reflects disease activity in childhood Crohn disease and ulcerative colitis

Abstract: These results show that in vitro ECP release from peripheral eosinophils reflects disease activity in both CD and ulcerative colitis and therefore can be used as a new appropriate laboratory parameter for assessment of disease activity in chronic inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…As far as we know, in no previous study have serum and faecal ECP levels in healthy children been specifically determined taking into consideration the influence of systemic eosinophilia and of IgE levels [20,25,29,30,33,34]. Most published data regard children with pathology and, as mentioned above, the few available data concerning healthy subjects correspond to small-sized control groups, not adequately selected and without established cut-offs [19,30,32,34].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As far as we know, in no previous study have serum and faecal ECP levels in healthy children been specifically determined taking into consideration the influence of systemic eosinophilia and of IgE levels [20,25,29,30,33,34]. Most published data regard children with pathology and, as mentioned above, the few available data concerning healthy subjects correspond to small-sized control groups, not adequately selected and without established cut-offs [19,30,32,34].…”
Section: Discussionmentioning
confidence: 96%
“…The specific cytoplasmatic granules of the eosinophils contain several proteins, 90 % of which are cationic: major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil protein X (EPX) and eosinophil-derived neurotoxin (EDN). As specific proteins of the eosinophils, they are excellent markers of their presence and activation [9,11,16,17,[21][22][23][24][25]. Recent studies in adults support their involvement in allergic asthma, allergic rhinitis, inflammatory bowel disease (IBD), coeliac disease and eosinophilic gastroenteritis (EOG).…”
Section: Introductionmentioning
confidence: 99%
“…However, U‐EPX seems to reflect not only allergic airway inflammation, but was shown to be increased in children with cystic fibrosis [16] or chronic tonsillitis [17]. Activation of the eosinophil has also been shown in children with chronic inflammatory bowel disease [18].…”
Section: Discussionmentioning
confidence: 99%
“…32 Luck et al showed a strong correlation between in-vitro ECP release of isolated peripheral-blood eosinophils and disease activity in a paediatric IBD population. 37 Coppi and colleagues investigated morphological activation patterns and chemotaxis of circulating eosinophils isolated from peripheral blood from Crohn's disease and ulcerative colitis patients as well as from healthy volunteers to understand whether eosinophils are activated before they home to the intestinal tissue in IBD. 38 They detected a pronounced chemotaxis in unstimulated eosinophils from patients in comparison to controls.…”
Section: Activation Of Eosinophils In Ibdmentioning
confidence: 99%